The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/scitranslmed.aaf2335
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of secreted antigen–targeted antibodies by the neonatal Fc receptor for precision imaging of the androgen receptor axis

Abstract: Targeting the androgen receptor (AR) pathway prolongs survival in patients with prostate cancer, but resistance rapidly develops. Understanding this resistance is confounded by a lack of noninvasive means to assess AR activity in vivo. We report intracellular accumulation of a secreted antigen-targeted antibody (SATA) that can be used to characterize disease, guide therapy, and monitor response. AR-regulated human kallikrein-related peptidase 2 (free hK2) is a prostate tissue-specific antigen produced in prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…We have developed an antibodybased platform that targets hK2, an enzyme that is prostate tissue-specific and under direct regulation of AR, the central driver of prostate adenocarcinoma. Our lead antibody, hu11B6, has been thoroughly evaluated for tumor detection and monitoring of disease activity by positron emission tomography and single photon emission computed tomography 12,14 . We have reported that hu11B6 can be applied for RIT applications 3,11,13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed an antibodybased platform that targets hK2, an enzyme that is prostate tissue-specific and under direct regulation of AR, the central driver of prostate adenocarcinoma. Our lead antibody, hu11B6, has been thoroughly evaluated for tumor detection and monitoring of disease activity by positron emission tomography and single photon emission computed tomography 12,14 . We have reported that hu11B6 can be applied for RIT applications 3,11,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously reported on the targeting specificity, efficacy and biological response of radiolabeled hu11B6 as an immunotheranostic vehicle. Preclinical evaluations have been carried out in multiple immunodeficient and immunocompetent, rodent disease models as well as in non-human primates 3,[11][12][13][14] . In addition, studies of the uptake mechanism have revealed that hu11B6 is internalized by hK2 expressing cells via a mechanism driven by the neonatal Fc receptor (FcRn); while uncomplexed hu11B6 is released from the cell by recycling endosomes after binding to FcRn, the hu11B6-hK2 complex is routed to lysosomes for processing 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many agents under development for improved detection and targeted therapy of prostate adenocarcinoma [15][16][17][18][19] . The widespread use of high-sensitivity and robust methods to detect PSMA in particular in the locally advanced and metastatic settings by PET and SPECT are poised to revolutionize management for those afflicted with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mice undergoing 18 F-DCFPyL PET imaging were administered radiotracer (7.4-9 MBq) either anesthetized (isoflurane) on camera with a tail vein catheter for kinetic studies, or via the retroorbital sinus for static images. A dedicated high resolution small animal PET scanner (R4, Concorde Microsystems; 7.8 cm axial by 10 cm transaxial field of view) was used to acquire whole body mouse scans (in the prone position) in list-mode configuration with a 350-700 keV energy range and a coincidence-timing window of 6 nsec for a minimum of 20x10 6 coincident events as previously described (28). PET image data were corrected for detector non-uniformity, dead time, random coincidences and physical decay and normalized to injected activity (determined by Capintec CR15 dose calibrator with setting #457).…”
Section: Mouse Pharmacokineticsmentioning
confidence: 99%